2007
DOI: 10.1002/cncr.22700
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bortezomib in patients with plasma cell leukemia

Abstract: A series of new cholesteric liquid‐crystalline polysiloxanes derived from steroid substituents were synthesized. The chemical structures of the monomers or polymers obtained were characterized by FTIR, element analyses, 1H NMR, and 13C NMR. Their mesogenic properties and thermal stability were investigated by differential scanning calorimetry, thermogravimetric analysis, polarizing optical microscopy, and X‐ray diffraction measurements. Monomers exhibited typical cholesteric focal‐conic or spiral texture. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
51
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 50 publications
(19 reference statements)
0
51
1
5
Order By: Relevance
“…No survival difference was observed between patients treated with bortezomib and those treated with old drugs, a result that does not confirm previous case reports. 7,8 This study is the largest series of patients with pPCL reported so far. It confirms the very poor prognosis specifically associated with pPCL.…”
mentioning
confidence: 97%
“…No survival difference was observed between patients treated with bortezomib and those treated with old drugs, a result that does not confirm previous case reports. 7,8 This study is the largest series of patients with pPCL reported so far. It confirms the very poor prognosis specifically associated with pPCL.…”
mentioning
confidence: 97%
“…In a retrospective survey of unselected cases of both sPCL and pPCL (Musto et al, 2007), 12 patients received bortezomib for 1-6 cycles, as single agent or variously combined with other drugs. Three patients were treated with bortezomib as frontline therapy, nine after 1-4 lines of chemotherapy, including ASCT and thalidomide, with overall responses in 92% of the patients [five partial response (PR), four very good partial response (VGPR) and 2 CR].…”
mentioning
confidence: 99%
“…Published response rates to bortezomib combination therapy in PPCL are promising. In the largest published series of PPCL patients treated with bortezomib, the median PFS and OS in patients with primary PCL had still not been reached at 21 months (the time of the report) [13].…”
Section: Durable Complete Remission Of Primary Plasma Cell Leukemia Wmentioning
confidence: 95%
“…There are a small number of reports on the utilization of bortezomib for PPCL [10][11][12][13][14][15][16][17][18][19][20]. Published response rates to bortezomib combination therapy in PPCL are promising.…”
Section: Durable Complete Remission Of Primary Plasma Cell Leukemia Wmentioning
confidence: 99%